La conservation-restauration en spectacle : les dessous des chefs-d’œuvre révélés dans les expositions - Claire Casedas (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The article deals with exhibitions about conservation-restoration. Between show and mediation, these events have a documentary and an educative purpose and they try to hightlight museum’s scientific and curatorial missions. These exhibitions allow to interest and explain to visitors the curators-restorators’ part in laboratories, when they are restoring and studying the cultural works. After describing the interest and different stakes of these exhibitions, the article describes the scenographic and educational tools. However, do these events show a real and an understanding image of conservation-restoration and its experts?